First Report of Peach Fruit Rot Caused by Fusarium avenaceum in Korea - A Yeong Heo; Young Mo Koo; Young-Joon Choi; Sang Hee Kim; Gyu Young Chung; Hyong Woo Choi (Research in Plant Disease, 2020)
In July 2019, typical rot symptom was observed on peach fruits harvested from the fields at Andong, Korea. As the disease progressed, white and purple colored mycelial mat developed on the surface of the infected fruits. A causal pathogen was isolated from the infected fruit and cultured on potato dextrose agar media for identification. Fungal colonies on potato dextrose agar produced 3 pigments, including purple, yellow, and white colors. The isolate incited fruit rot symptoms on artificially inoculated peach fruits, from which the same fungus was isolated, fulfilling Koch’s postulates. Based on the morphological characteristics and sequence analysis of rDNA internal transcribed spacer, translation elongation factor 1-alpha, and β-tubulin, the causal agent of the disease was identified as Fusarium avenaceum. This study is the first report of fruit rot of peach fruits caused by Fusarium avenaceum in Korea.